A bi-level multi-objective optimal operation of grid-connected microgrids - Lv, Tianguang; Ai, Qian; Zhao, Yuanyuan (Electric power systems research, 2016)
•Provide a dispatch method for DN–MG system, considering both benefit of MG and DN.•Optimize system operation considering power quality, economy and energy utilization.•Apply a combination of algorithms into a multi-objective bi-level programming.•The proposed algorithm can be used in complex master-slave power systems. To obtain operation benefits of both distribution network (DN) and microgrids (MGs), a multi-objective bi-level optimal operation model for DN with grid-connected MGs is explained. Starting from forecast of load and generation in MGs, upper-level (DN level) model determines the optimal dispatch of DN to achieve its power loss reduction and voltage profile improvement. Lower-level (MG level) model accepts the dispatch requirements from upper-level and determines the optimal operation strategy of distributed generators in MGs. Their energy utilization is increased with the consideration of wind curtailment, solar curtailment and other factors such as environmental benefits. With the mutual influence and constraints between upper-level and lower-level model, MGs could accommodate the optimal dispatch of DN. To solve the bi-level model, a combination method based on self-adaptive genetic algorithm and non-linear programming is put forward. IEEE 33 DN with Europe typical MGs and a real system are presented to perform several simulations, and results show the over-all optimal operation schemes of both DN and MGs compared with traditional dispatch approach, thereby validating the efficiency of the proposed model.